A Qualitative Evaluation of the Performance-based Supplementary Payment System in Turkey: Physicians' Perspectives. (June 2014) - Yuzden, Ganime Esra; Yildirim, Julide
The Ministry of Health of Turkey introduced performance-based supplementary payment (PBSP) system in 2004. The importance of feedbacks from healthcare providers regarding the implementation of alternative health policies has been recognized in the literature. This study reports the perceptions of physicians about the PBSP system in Turkey. A qualitative analysis has been conducted in two hospitals in the Western province of Turkey, Balıkesir. Analysis results suggest that physicians have limited awareness about the pay for performance system. They agree that the PBSP system has not achieved the objectives of enhancing productivity, efficiency and quality of care. The major contributing factors to the limited success of the system have been identified as increased workload, stress and competition among the physicians. Thus revisions have been suggested for the proper implementation of the programme, which include the determination of a maximum number of medical examinations.